Penerapan Projek Penguatan Profil Pelajar Pancasila (P5) Melalui Kegiatan Sosiodrama Sebagai Upaya Preventif Perbuatan Perundungan - Moh. Thoyyib; Giati Anisah; Siti Khoiriyah; Ahmad Shofiyuddin (Institut Agama Islam Al-Hikmah Tuban, 2023)
In line with the values of the Pancasila profile which always emphasizes student personality based on the Pancasila profile, cases of bullying have started to rise which seem to become a tradition especially in the school environment where the school environment which was originally the most comfortable place in learning has now turned into a place full of suffering for victims of bullying. in the school environment. Therefore this study aims, Knowing the form of P5 activities which include the process and stages of Implementation of the Pancasila Student Profile Strengthening Project through sociodrama activities as an effort to anticipate bullying acts and also to find out the results of the Implementation of the Pancasila Student Profile Strengthening Project Implementation through sociodrama activities as an effort to anticipate acts of bullying . This study uses a qualitative approach with a descriptive type with the results of the research in the form of an elaboration of the stages of preparation, process, results and evaluation in implementing the project to strengthen the profile of Pancasila students.